Comparing the effectiveness of two models of initial teacher education programmes in Israel: concurrent vs. consecutive - Zuzovsky, Ruth; Donitsa-Schmidt, Smadar (European Journal of Teacher Education, 2017)
The purpose of the present study was to examine the effectiveness of two common models of initial teacher education programmes that are prevalent in many countries, including Israel. The two are: the concurrent model, in which disciplinary studies and pedagogical studies are integrated and taught at the same time; and the consecutive model, which focuses mostly on pedagogy following the disciplinary studies already completed by university graduates interested to go into teaching. The study followed two cohorts of graduates who completed their studies in teacher colleges in Israel in the years 2005–2006 for a period of 10 years, a total of 11,978 graduates. Out of them, 10,428 studied in the concurrent model and 1550 in the consecutive model. To compare the effectiveness of the two models, efficiency and equity measures were used. The findings of the study indicate the advantage of the consecutive model in most of the measures examined.